2014
DOI: 10.1167/iovs.12-11462
|View full text |Cite
|
Sign up to set email alerts
|

Myopia Control With Positively Aspherized Progressive Addition Lenses: A 2-Year, Multicenter, Randomized, Controlled Trial

Abstract: To the extent that has been tested and that can be tolerated by wearers of spectacle lenses, the high positive aspherization of the distance zone added to PALs does not enhance their therapeutic efficacy in slowing myopia progression. (http://www.anzctr.org.au/ number, ACTRN12608000566336).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 47 publications
2
65
0
2
Order By: Relevance
“…Benchmark PAL and SVL PAL 2 has been used already in a clinical trial to investigate its efficacy in reducing progression of myopia in children. 21 There was a statistically significant (P ¼ 0.02) retardation of myopia progression (0.27 6 0.11 D, equivalent to a reduction ratio of 20%) during the 24-month period of the trial (0.24 D of which has occurred in the first 12 months) for the positively aspherized PAL with the 1.5 D of add power, when compared with a SVL control group. 21 The reduction of myopia progression using the PA-PAL and 1.50 D add power was within the range of reported retardations of myopia from earlier trials that used standard PALs.…”
Section: La With Svl Distance and Near Correctionmentioning
confidence: 87%
See 3 more Smart Citations
“…Benchmark PAL and SVL PAL 2 has been used already in a clinical trial to investigate its efficacy in reducing progression of myopia in children. 21 There was a statistically significant (P ¼ 0.02) retardation of myopia progression (0.27 6 0.11 D, equivalent to a reduction ratio of 20%) during the 24-month period of the trial (0.24 D of which has occurred in the first 12 months) for the positively aspherized PAL with the 1.5 D of add power, when compared with a SVL control group. 21 The reduction of myopia progression using the PA-PAL and 1.50 D add power was within the range of reported retardations of myopia from earlier trials that used standard PALs.…”
Section: La With Svl Distance and Near Correctionmentioning
confidence: 87%
“…21 There was a statistically significant (P ¼ 0.02) retardation of myopia progression (0.27 6 0.11 D, equivalent to a reduction ratio of 20%) during the 24-month period of the trial (0.24 D of which has occurred in the first 12 months) for the positively aspherized PAL with the 1.5 D of add power, when compared with a SVL control group. 21 The reduction of myopia progression using the PA-PAL and 1.50 D add power was within the range of reported retardations of myopia from earlier trials that used standard PALs. Standard single vision spherical lenses lead to higher lags of accommodation than the benchmark lens, indicating that the progressive addition lens is effective in the reduction of the LA.…”
Section: La With Svl Distance and Near Correctionmentioning
confidence: 87%
See 2 more Smart Citations
“…[97][98][99][100][101][102][103][104][105][106] There are controversies with regard to the use of progressive addition and bifocal spectacles for MC, as some studies have found larger treatment effects occurring over a period of at least two years of lens wear, 12,107 whereas others carried out with progressive addition lenses designed to reduce peripheral hyperopic defocus have found minimal impact on reducing myopia progression. 108,109 Despite this, spectacle designs for MC are a necessary consideration, particularly in cases where other treatment options are not feasible (e.g., very young children, those unable to wear contact lenses due to access or cost, situations associated with poor hygiene conditions, or remote locations far from specialized eye care). Furthermore, a reserve pair of spectacles to the most recent prescription is always recommended for contact lens wearers.…”
Section: Regulatory Process For Marketing Medicalmentioning
confidence: 99%